PERAN BRAND IMAGE SEBAGAI MEDIATOR ANTARA COUNTRY OF ORIGIN TERHADAP PURCHASE INTENTION (Studi Pada Produk Laptop Sony Vaio di Kota Denpasar) - Nata Arimbawa, Cokorda Agung; Rahyuda, I Ketut (E-Jurnal Manajemen, 2015)
Globalization and IT is becoming a center of attention of local and international community of marketers develop electronic products to attract consumers' purchasing intentions. It is important to understand the consumer behavior towards electronic product that has the country of origin and brand image for contrasted from other products. This study aims to determine the role of brand image and the country of origin as a predictor of purchase intention Sony Vaio laptop brands in Denpasar. Collecting data using questionnaires with non-probability sampling method on 100 respondents from all regions of the city of Denpasar. Analysis of the data using PLS analysis method (Partial Least Square) with the help of software Smart PLS 3.1.3. The results of this study indicate that the country of origin has a positive and significant impact on the brand image and purchase intention on the product Sony Vaio laptop. But the brand image as a mediating variable has a weaker effect than the direct influence of country of origin of the purchase intention. Based on the results of the study, respondents in Denpasar able to apply shape consumer behavior to determine country of origin information and brand image of a product. Consumers have the intention to buy the products - products that have the country's image and brand image, especially Laptops Sony Vaio brand. This is due to the respondent is able to assess and differentiate products that have a country of origin and brand image of the product. Although not yet reached the willingness to buy, but this can be a potential market for the company Sony to focus on market segment based on the characteristics of the respondents, communicate excellence image of the country and the brand image roduk Sony Vaio Laptop, and educate the market to switch to a product - products that have a country of origin information and brand image, so it is expected to increase intention to purchase products Sony Vaio Laptop.
Keywords: Country Of Origin, Brand Image, Purchase Intention